Brain site-specific proteome changes in aging-related dementia - Manavalan, Arulmani (Nature Publishing Group, 2013)
This study is aimed at gaining insights into the brain site-specific proteomic senescence signature while comparing physiologically aged brains with aging-related dementia brains (for example, Alzheimer's disease (AD)). Our study of proteomic differences within the hippocampus (Hp), parietal cortex (pCx) and cerebellum (Cb) could provide conceptual insights into the molecular mechanisms involved in aging-related neurodegeneration. Using an isobaric tag for relative and absolute quantitation (iTRAQ)-based two-dimensional liquid chromatography coupled with tandem mass spectrometry (2D-LC-MS/MS) brain site-specific proteomic strategy, we identified 950 proteins in the Hp, pCx and Cb of AD brains. Of these proteins, 31 were significantly altered. Most of the differentially regulated proteins are involved in molecular transport, nervous system development, synaptic plasticity and apoptosis. Particularly, proteins such as Gelsolin (GSN), Tenascin-R (TNR) and AHNAK could potentially act as novel biomarkers of aging-related neurodegeneration. Importantly, our Ingenuity Pathway Analysis (IPA)-based network analysis further revealed ubiquitin C (UBC) as a pivotal protein to interact with diverse AD-associated pathophysiological molecular factors and suggests the reduced ubiquitin proteasome degradation system (UPS) as one of the causative factors of AD.